Preparation method of lead-free thin-wall tubular texture piezoelectric ceramic

By filling corundum powder on the inside and outside of the ceramic blank and using porous hollow bricks, the problem of uneven deformation and shrinkage of ceramic thin-walled round tubes during high-temperature sintering is solved, and a lead-free thin-walled round tube type with high texture and stable performance is achieved Preparation of textured piezoelectric ceramics.

CN119219397APending Publication Date: 2024-12-31XIAN TECH UNIV
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411347733.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-26
Publication Date
2024-12-31

AI Technical Summary

Technical Problem

When preparing piezoelectric ceramic thin-walled round tubes, the high content of organic carriers in the ceramic blank leads to defects such as deformation, cracking or bubbling during heating, affecting the texture and piezoelectric properties of the ceramic, especially for large-size thin-walled ceramics. Deformation uniformity is difficult to control.

Method used

Cylindrical alumina crucible and cylindrical hollow bricks are placed on the inside and outside of lead-free thin-walled round tube-type textured piezoelectric ceramic blank, and corundum powder is filled in the gaps to ensure the blank during glue discharge and sintering. The direction is uniformly subjected to force, and alumina powder and porous hollow bricks calcined at 1400°C are used to adsorb organic matter and control shrinkage.

Benefits of technology

The high texture degree of lead-free thin-walled round tube-type textured piezoelectric ceramics is achieved (up to 94.19%), ensuring the regularity of the shape and stable performance of the blank, simplifying the process, and suitable for industrial production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119219397A_ABST
    Figure CN119219397A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of lead-free thin-wall tubular texture piezoelectric ceramics, which comprises the following steps: respectively placing a cylindrical hollow brick and an alumina crucible on the inner side and the outer side of a lead-free thin-wall tubular texture piezoelectric ceramic biscuit, and filling corundum powder in gaps and the bottom formed by the inner side and the outer side of the biscuit, the hollow brick and the crucible; the preparation method comprises the following steps of: performing glue discharging and sintering on a green body to ensure that the green body is uniformly stressed in all directions in glue discharging and sintering processes and plays a role in supporting the green body, and then performing glue discharging, isostatic pressing treatment and sintering molding to obtain the lead-free thin-wall tubular textured piezoelectric ceramic. The preparation method is simple, the process is easy to control, industrial production, popularization and application are easy, and the texture degree of the prepared lead-free thin-wall tubular texture piezoelectric ceramic is as high as 94.19%.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of special-shaped ceramic preparation, and relates to a method for preparing lead-free thin-walled circular tube-type textured piezoelectric ceramics. Background Art

[0002] Underwater acoustic communication and underwater detection play an important role in the fields of maritime military, marine development and scientific research. Sonar is known as the "wind-hearing" and "clairvoyant" in the sea and is widely used in ocean detection and underwater acoustic communication. The underwater acoustic transducer is the key part of sonar, so it is of great significance to study high-performance underwater acoustic transducers.

[0003] Piezoelectric ceramic transducers have the characteristics of high electromechanical conversion efficiency, high power density, stable performance, and simple structure, and they are the best in underwater acoustic transducers. In the development of piezoelectric transducers, it is crucial to improve the electrical properties of piezoelectric ceramics. The texturing of ceramics can make piezoelectric materials more sensitive to electric fields or mechanical stresses in a specific direction, thereby improving their piezoelectric coefficients, electromechanical coupling coefficients, and optimizing energy conversion efficiency. In addition to improving the electrical properties of piezoelectric ceramic materials, optimizing transducer design is another factor that affects transducer efficiency. The radial vibration circular tube piezoelectric transducer has the advantages of large radiation area, high radiation efficiency, uniform directivity, high receiving sensitivity, and stable performance. Therefore, the combination of ceramic texturing and circular tube material design is a good direction for the design and development of piezoelectric ceramic transducers at this stage and even in the future.

[0004] Due to the unique preparation process of textured ceramics, ceramic blanks often contain a high amount of organic carriers, with a mass ratio of usually 15-25%, and some even as high as 30% or more. These organic substances decompose and volatilize during the heating process. Improper process control will cause defects such as deformation, cracking or bubbling of the blank, which seriously affects the radial orientation arrangement of the template in the circular tube textured ceramic blank. In addition, during the high-temperature sintering process, the ceramic tube will undergo densification and template-induced grain growth, and will shrink significantly. If there is uneven shrinkage in the radial or height direction, it will seriously affect the orientation consistency of the ceramic grains, resulting in a significant decrease in texture and piezoelectric performance. Especially for large-sized thin-walled (t≤2.5mm) textured ceramic circular tubes, it is more difficult to control the uniformity of deformation during the blank debinding and sintering process, and the dimensional tolerance requirements are more stringent.

[0005] In summary, the debinding and sintering of the textured piezoelectric ceramic thin-walled round tube blank are the most critical steps in the entire preparation process of the piezoelectric ceramic thin-walled round tube. Based on this, the present invention aims to provide a method for debinding and sintering of a lead-free thin-walled round tube textured piezoelectric ceramic blank, which is suitable for a lead-free textured piezoelectric ceramic system. Summary of the invention

[0006] In view of the above technical problems, the present invention aims to provide a method for preparing lead-free thin-walled circular tubular textured piezoelectric ceramics, wherein cylindrical hollow bricks and alumina crucibles are respectively placed on the inner and outer sides of the lead-free thin-walled circular tubular textured piezoelectric ceramic blank, and corundum powder is filled in the gaps formed by the inner and outer sides of the blank and the hollow bricks and the crucible and at the bottom to ensure that the blank is subjected to uniform force in all directions during the debinding and sintering process and to support the blank, and then the lead-free thin-walled circular tubular textured piezoelectric ceramics are obtained through debinding, isostatic pressing and sintering. The preparation method of the present invention is simple, the process is easy to control, and it is easy to industrialize production and promote application. The texture degree of the prepared lead-free thin-walled circular tubular textured piezoelectric ceramics is as high as 94.19%.

[0007] To achieve the above object, the technical solution adopted by the present invention is:

[0008] A method for preparing a lead-free thin-walled circular tubular textured piezoelectric ceramic is carried out in the following steps in sequence:

[0009] (1) filling the bottom of a cylindrical alumina crucible with a height of 10 to 50 mm with corundum powder and compacting it, placing the rolled lead-free thin-walled circular tubular textured piezoelectric ceramic blank in the alumina crucible filled with corundum powder, and placing a cylindrical hollow brick at the center of the lead-free thin-walled circular tubular textured piezoelectric ceramic blank;

[0010] In this step, the corundum powder filled at a height of 10 to 50 mm at the bottom of the alumina crucible is crucial for the subsequent debinding and sintering process, which is specifically reflected in:

[0011] (i) The filled corundum powder will adsorb organic matter in the sample through capillary action;

[0012] (ii) The corundum powder filled at the bottom has a certain bearing capacity for the sample, which prevents the corundum powder from being too loose during the debinding process, causing the sample to sink unevenly, thereby causing it to tilt, generate shear force, and destroy the arrangement of the template;

[0013] (iii) Used to fix the cylindrical hollow bricks used in the process of glue removal molding. Since the hollow bricks cannot be tilted during the entire molding process, once tilted, shear force will be generated, causing shear deformation of the sample. Therefore, the hollow bricks must be fixed firmly;

[0014] (iv) To ensure the uniformity of the temperature field of the sample, the corundum powder filled at the bottom of the crucible with a height of 10 to 50 mm can keep the sample at a certain distance from the bottom of the crucible during the molding process, thereby ensuring the uniformity and consistency of the temperature field of the sample and avoiding the inconsistent deformation and shrinkage of the sample due to local temperature differences;

[0015] (2) filling the gaps between the lead-free thin-walled circular tubular textured piezoelectric ceramic blank, the outer cylindrical alumina crucible, and the inner cylindrical hollow brick with corundum powder, respectively, cleaning the excess powder, and placing it in a muffle furnace for debinding;

[0016] The present invention must use a cylindrical crucible and a cylindrical hollow brick with a porosity of 48-52% during the debinding process because the shape of the crucible and the shape of the hollow brick will directly affect the yield of the powder (corundum powder) during the debinding process. Irregular shapes will cause the yield of the powder to be different in different places, and the yield space will be different. Areas with small yield spaces will limit the shrinkage of the sample, resulting in inconsistent force and different shrinkage amounts on the sample during the debinding and shrinking process, thereby causing deformation of the sample. Therefore, when selecting the shape of the outer crucible and the inner hollow brick, it is necessary to ensure that the powder is isotropic when it yields inside, so that the force in all directions during the powder yield process is uniform, and the forces acting on the sample in all directions during the shrinkage process are also the same, providing a prerequisite guarantee for maintaining the regularity of the sample shape;

[0017] (3) isostatic pressing the sample after debinding;

[0018] (4) The sample after isostatic pressing is placed on an alumina plate covered with corundum powder. A cylindrical hollow brick is placed at the center of the sample, and corundum powder is filled in the gap. Matrix powder with the same composition as the sample is placed on the periphery and placed in a muffle furnace for sintering.

[0019] As a limitation of the preparation method of the present invention, in step (1), the corundum powder is a powder calcined at 1400° C. for 2 hours, and the particle size of the powder is 150 to 350 meshes.

[0020] Corundum powder must be calcined before use. On the one hand, it can avoid the influence of powder deformation on sample debinding. On the other hand, it can make the powder undergo phase transformation at a specific temperature to form a spherical morphology structure, ensuring that it has good adsorption and good powder fluidity.

[0021] As we all know, the main component of corundum powder is alumina. The original alumina powder (corundum powder) is mainly composed of four alumina phases: γ-Al2O3, δ-Al2O3, θ-Al2O3 and α-Al2O3. The microstructure of α-Al2O3 is spherical, with good fluidity and adsorption properties. It plays an adsorption and permeability role in the debinding process. The good fluidity not only plays a solid role, but also does not limit the shrinkage of the ceramic body during debinding and sintering. Therefore, γ-Al2O3, δ-Al2O3 and θ-Al2O3 phases must be converted into α-Al2O3 phases; since the phase transformation of γ-Al2O3, δ-Al2O3 and θ-Al2O3 to α-Al2O3 is reconstructed and carried out through nucleation and growth processes, a relatively high activation energy is required, and most of the activation energy is used for the nucleation process, so in order to overcome the nucleation barrier, it is necessary to increase the temperature. After calcination at 700℃, 800℃ and 900℃, the phase of alumina powder did not change, and the microscopic morphology did not change much; after calcination at 1000℃, the phase changed significantly, γ-Al2O3 and δ-Al2O3 transformed into θ-Al2O3 and α-Al2O3, the microscopic morphology of alumina powder changed, irregular small grains began to appear, and the grain boundaries between the small grains were obvious; after calcination at 1100℃, most of θ-Al2O3 was transformed into α-Al2O3, and the small grains separated from each other to form cracks. gap; after the calcination temperature reaches 1200℃, all the transition phases of alumina are transformed into α-Al2O3, and some small grains grow together because of growth; when the temperature continues to rise to 1400℃, the grains grow further and gradually grow into small spheres or ellipsoids. At this time, the alumina powder has good adsorption and fluidity; but when the calcination temperature is greater than 1400℃, the grains will grow further and overburning is likely to occur, thus affecting the adsorption and fluidity of the powder. Therefore, 1400℃ is selected as the calcination temperature of alumina powder.

[0022] The calcination time of alumina powder will affect its microscopic morphology and structure. When the calcination time is greater than 2h, the adsorption performance of alumina powder will deteriorate; but when the calcination time is less than 2h, the alumina powder grains cannot grow completely and uniform spherical grains cannot be guaranteed.

[0023] The particle size of corundum powder will also affect the final quality of the sample. The present invention selects corundum powder with a particle size of 150-350 mesh. The corundum powder with this particle size has a large specific surface area, high porosity, strong adsorption capacity, and good fluidity. The gaps between the particles will not be very small when they are aggregated, so that the overall air permeability and heat transfer are good, which is conducive to the volatilization of organic matter, can reduce the loss of manpower and fuel, has a good debinding effect, and a high yield rate of workpieces; when the powder particle size is greater than 150-350 mesh, the powder particles are too fine, and the particles are The particles gather together and bite each other to form arch bridge pores, and the overall fluidity is poor, which causes blistering, cracking, deformation and other phenomena in the part of the sample without powder support during the debinding process. In addition, the gaps between the particles are small when they are gathered, resulting in poor overall air permeability and heat transfer, which is not conducive to the volatilization of organic matter. When the powder particle size is less than 150-350 mesh, the powder particles are coarse, and its own fluidity will deteriorate, and the powder has poor yieldability, resulting in excessive constraint on the sample during the shrinkage process, which is easy to cause the sample to crack.

[0024] As another limitation of the preparation method of the present invention, in step (1), the hollow brick is made of high temperature resistant porous mullite with a porosity of 48-52%; the diameter of the hollow brick is 5-60 mm and the height is 5-80 mm.

[0025] The hollow brick material of the present invention is a porous high-temperature resistant material because when the organic content in the sample is large, the adsorption of the corundum powder cannot be satisfied, and part of the organic matter will escape in the form of gas through the corundum powder. At this time, hollow bricks are needed to supplement the adsorption, and the porosity of the hollow brick will affect the degree of adsorption. If the porosity of the hollow brick is greater than 48-52%, the filled corundum powder will enter the size of the hollow brick, affecting the solidification ability of the corundum powder to the sample, and also affecting the escape of organic gas during the sample molding process; but when the porosity of the hollow brick is less than 48-52%, the organic gas in the sample will not be able to escape, thereby affecting the surface quality of the sample and causing defects.

[0026] As the third limitation of the preparation method of the present invention, in step (2), the corundum powder is a powder calcined at 1400° C. for 2 hours, and the powder particle size is 150 to 350 meshes; and the filling powder width is 5 to 25 mm.

[0027] The powder filling width formed by the lead-free thin-walled circular tubular textured piezoelectric ceramic blank, the crucible and the internal hollow brick is also a major factor affecting the sample forming, because the width of the powder filling will directly affect the adsorption force of the corundum powder. If the powder filling width is less than 5-25mm, the adsorption force of the corundum powder is insufficient, which will cause defects on the sample surface, and the gas generated by the organic matter inside the sample at high temperature will directly break through the sample surface and cause the corundum powder to agglomerate. The agglomeration of the powder is not favorable during the sample shrinkage process, and will cause the sample to encounter too much resistance during the shrinkage process. On the one hand, it will cause the sample to be unable to maintain a regular shape. On the other hand, the sample will rupture due to the low strength of the sample after the organic matter is removed. However, when the powder filling width is greater than 5-25mm, due to excessive filling of powder, the sample will encounter too much resistance during the shrinkage process, which can easily cause the sample to rupture during the forming process.

[0028] As a fourth limitation of the preparation method of the present invention, in step (2), the debinding process is carried out in the following order:

[0029] (a) The first heating stage: from room temperature to 190°C, and keep the temperature for 10 hours;

[0030] (b) The second heating stage, from 190°C to 240°C, kept for 10 h;

[0031] (c) The third heating stage, from 240°C to 280°C, and kept for 5 hours;

[0032] (d) The fourth heating stage, from 280°C to 380°C, and kept for 5 hours;

[0033] (e) The fifth heating stage, from 380°C to 550°C, kept for 2 h;

[0034] (f) Cooling stage: the temperature is reduced from 550°C to 150°C, and then cooled to room temperature in the furnace.

[0035] As is known to all, the debinding process of textured piezoelectric ceramics has a great influence on the shape, size and performance of the final product, so it is necessary to achieve the desired debinding effect by controlling the temperature, time and heating rate. The first stage of the debinding process of the present invention is from room temperature to 190°C. In this stage, the residual organic solvent in the sample will volatilize, and the binder, plasticizer and other organic substances will soften. The insulation time in this stage should not be too long. Too long insulation time will lead to too long softening time of organic matter, which will easily cause deformation of the sample. However, it should not be too short either. Too short insulation time is not conducive to improving the adsorption degree of corundum powder for solvents and organic matter. At the same time, too short insulation time is not conducive to the discharge of gas generated after solvent volatilization, and the residual gas will easily damage the surface of the sample. In this experiment, it is best to keep warm for 10 hours; the second stage is from 190°C to 240°C. In this stage, Organic matter (mainly alcohols) begins to decompose, and gas and colloid substances will be produced. The insulation time of this stage is 10 hours. If it is longer than 10 hours, the sample will be in a softened state for a long time, which will cause the sample to deform easily and also cause energy waste. However, if the insulation time is too short (less than 10 hours), the remaining organic gas in the sample cannot escape evenly and smoothly during the heating stage, and will gather in the sample, thereby damaging the sample surface. The third stage is from 240℃ to 280℃. In this stage, the remaining organic matter in the sample will decompose (mainly esters). If the insulation time of this stage is longer than 5 hours, the sample will be prone to Deformation, less than 5h will lead to incomplete decomposition of organic matter, and the generated gas cannot be discharged in time, accumulates in the sample and generates stress, resulting in sample defects; the fourth stage is from 280℃ to 380℃, at this stage the sample begins to shrink, the insulation time is too long (more than 5h), it will cause waste of resources and reduce production efficiency, less than 5h will lead to the stress generated during the shrinkage of the sample cannot be completely released, thus causing the sample to rupture; the fifth stage is from 380℃ to 550℃, at this stage the residual organic matter and the secondary decomposition products of organic matter will be further decomposed into small molecules, accompanied by further volatilization, this stage If the holding time is longer than 2h, the small molecule substance (which is not easy to solidify and is in a softened state at this temperature) will exist in the sample for too long. At this time, the sample has begun to shrink, which can easily change the shape of the sample. If the holding time is shorter than 2h, the gas will escape too quickly and break through the surface of the sample. In the cooling stage, the temperature is first reduced from 550℃ to 150℃ because it is necessary to ensure the release of thermal stress inside the sample during the cooling process. If the stress is released too quickly, it will affect the shape of the sample on the one hand, and on the other hand, if the thermal stress is released too quickly, it will affect the arrangement of the BT template inside the sample. Therefore, the temperature should be reduced to 150℃ first and then cooled to room temperature with the furnace.

[0036] As a fifth limitation of the preparation method of the present invention, in step (3), the isostatic pressure is 100-200 MPa and the time is 5-10 min.

[0037] As a sixth limitation of the preparation method of the present invention, in step (4), the corundum powder is a powder calcined at 1400° C. for 2 hours, and the powder particle size is 100 to 200 meshes.

[0038] As the seventh limitation of the preparation method of the present invention, in step (4), the diameter of the hollow brick is 5 to 60 mm and the height is 5 to 80 mm.

[0039] As an eighth limitation of the preparation method of the present invention, the wall thickness t of the lead-free thin-walled circular tubular textured piezoelectric ceramic is ≤2.5 mm; and the texture degree of the lead-free thin-walled circular tubular textured piezoelectric ceramic is 94.19%.

[0040] As a further limitation of the preparation method of the present invention, in step (2), the heating rate of the first heating stage is 0.1-0.3°C / min; the heating rate of the second heating stage is 0.1°C / min; the heating rate of the third heating stage is 0.1°C / min; the heating rate of the fourth heating stage is 0.1°C / min; the heating rate of the fifth heating stage is 0.1°C / min; and the rate of the cooling stage is 0.2-0.5°C / min.

[0041] The present invention adopts a relatively small heating rate. When the heating rate in the first heating stage is less than 0.1-0.3°C / min, the debinding time will be prolonged. When the heating rate is greater than 0.1-0.3°C / min, the solvent will evaporate too quickly, affecting the surface quality of the sample. When the heating rate in the second heating stage is greater than 0.1°C / min, the gas release rate of the decomposed alcohol substance will be too fast. When it is less than 0.1°C / min, the softened alcohol organic matter will be retained in the sample for too long, and the sample cannot be guaranteed to be in a complete tubular shape. When the heating rate in the third heating stage is greater than 0.1°C / min, the gas release rate of the decomposed ester substance will be too fast. When it is less than 0.1°C / min, the softened ester organic matter will be The retention time in the sample is too long; when the heating rate in the fourth heating stage is greater than 0.1℃ / min, the sample will not shrink uniformly during the shrinkage process and the final shape cannot be guaranteed. When it is less than 0.1℃ / min, the gas escape rate of the decomposition of organic matter will be too fast. When the heating rate in the fifth heating stage is greater than 0.1℃ / min, the gas escape rate of the remaining organic matter and the secondary decomposition products of the organic matter in the sample will be fast enough. When it is less than 0.1℃ / min, the sample debinding process will be prolonged, affecting the efficiency. When the cooling rate is greater than 0.2~0.5℃ / min, the thermal stress inside the sample will be released too quickly. When it is less than 0.2~0.5℃ / min, the sample will not be able to shrink completely and more voids will appear inside.

[0042] The above technical solution of the present invention is taken as a whole, and each step is closely related and influences each other, which jointly determine the morphological characteristics and performance of the product.

[0043] The above technical solution has the following advantages or beneficial effects:

[0044] 1. The preparation method of the present invention is simple, the process is easy to control, and it is easy to industrialize production and promote application.

[0045] 2. The present invention uses a cylindrical alumina crucible and a cylindrical hollow brick during the debinding and sintering process, so that the yield of the lead-free thin-walled circular tubular textured piezoelectric ceramic blank remains consistent at all locations during the shrinkage process, and the force in all directions during the yielding process is uniform, thereby ensuring the shape regularity of the sample.

[0046] 3. In the process of debinding and sintering, the present invention uses porous hollow bricks and corundum powder to synergistically adsorb organic matter. When the organic matter content is large and the adsorption performance of the corundum powder cannot meet the requirements, part of the organic matter will escape through the powder in the form of gas. At this time, the porous hollow bricks will supplement the adsorption of organic matter to prevent bubbling, cracking and deformation of the green body.

[0047] 4. The method for preparing a lead-free thin-walled circular tubular textured piezoelectric ceramic provided by the present invention has a wide range of applications, and the texture degree of the prepared lead-free thin-walled circular tubular textured piezoelectric ceramic is as high as 94.19%.

[0048] The invention is suitable for preparing lead-free thin-wall circular tube type textured piezoelectric ceramics.

[0049] The technical solution of the present invention will be further described in detail below in conjunction with the accompanying drawings and specific implementation methods. BRIEF DESCRIPTION OF THE DRAWINGS

[0050] Figure 1 This is a blank image of the lead-free thin-walled circular tubular textured piezoelectric ceramics prepared in Examples 1-4 of the present invention after debinding and molding, wherein: Figure 1 (a) is a blank image after debinding molding in Example 1, Figure 1 (b) is a blank image after debinding molding in Example 2. Figure 1 (c) is a blank image after debinding molding in Example 3. Figure 1 (d) is a blank image after debinding and molding in Example 4;

[0051] Figure 2 This is a sample picture of the lead-free thin-walled circular tubular textured piezoelectric ceramics prepared in Examples 1-4 of the present invention after sintering and without processing, wherein: Figure 2 (a) is a sample image after sintering in Example 1. Figure 2 (b) is a sample image after sintering in Example 2. Figure 2(c) is a sample image after sintering in Example 3. Figure 2 (d) is a picture of the sample after sintering in Example 4;

[0052] Figure 3 XRD spectrum and texture degree of the lead-free thin-walled circular tubular textured piezoelectric ceramic prepared in Example 3 of the present invention;

[0053] Figure 4 This is a cross-sectional scan of the lead-free thin-walled circular tubular textured piezoelectric ceramic prepared in Example 3 of the present invention;

[0054] Figure 5 This is a blank image of the lead-free thin-walled circular tubular textured piezoelectric ceramic prepared in Comparative Example 1-2 of the present invention after debinding and molding, wherein: Figure 5 (a) is the sample blank image after debinding molding in comparative example 1, Figure 5 (b) is a blank image of the sample after debinding molding in comparative example 2;

[0055] Figure 6 This is a sample blank image after debinding molding in Comparative Example 3 of the present invention;

[0056] Figure 7 This is a sample blank image after debinding molding in Comparative Example 4 of the present invention;

[0057] Figure 8 This is a sample blank image after debinding molding in Comparative Example 5 of the present invention;

[0058] Fig. 9 This is a sample blank image after debinding molding in Comparative Example 6 of the present invention;

[0059] Fig.10 This is a sample blank image after debinding molding in Comparative Example 7 of the present invention, wherein: Fig.10 (a) is the macroscopic morphology of the sample after debinding. Fig.10 (b) is the internal powder status diagram. DETAILED DESCRIPTION

[0060] The following embodiments are only some embodiments of the present invention, rather than all embodiments. Therefore, the detailed description in the embodiments of the present invention provided below is not intended to limit the scope of the present invention claimed for protection, but merely represents selected embodiments of the present invention. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without making creative work belong to the protection scope of the present invention.

[0061] In the present invention, unless otherwise specified, all equipment and raw materials can be purchased from the market or are commonly used in the industry. The methods in the following embodiments are all conventional methods in the art unless otherwise specified.

[0062] Example 1

[0063] This embodiment prepares a lead-free thin-walled circular tube-shaped textured piezoelectric ceramic, and the preparation process and steps are as follows:

[0064] (1) The bottom of a cylindrical alumina crucible is filled with corundum powder calcined at 1400° C. for 2 hours and compacted. The height of the filled corundum powder is 30 mm and the particle size is 150-350 meshes. A rolled lead-free thin-walled circular tubular textured piezoelectric ceramic blank with an inner diameter of Φ=54 mm, a height of h=10.75 mm, and a wall thickness of t=1.72 mm is placed in the alumina crucible, and a cylindrical hollow brick with a diameter of 5 mm, a height of 32 mm, and a porosity of 48% is placed at the center of the lead-free thin-walled circular tubular textured piezoelectric ceramic blank;

[0065] (2) The gaps formed by the lead-free thin-walled circular tubular textured piezoelectric ceramic blank, the cylindrical alumina crucible and the cylindrical hollow brick were filled with corundum powder with a width of 25 mm and 25 mm respectively, which was calcined at 1400°C for 2 hours. The particle size of the corundum powder was 150-350 meshes. After the excess powder was cleaned, it was placed in a muffle furnace for debinding. The debinding process was as follows:

[0066] First, increase the temperature from room temperature to 190℃ at a rate of 0.1℃ / min, and keep it for 10h. Then, increase the temperature from 190℃ to 240℃ at a rate of 0.1℃ / min, and keep it for 10h. Then, increase the temperature from 240℃ to 280℃ at a rate of 0.1℃ / min, and keep it for 5h. Then, increase the temperature from 280℃ to 380℃ at a rate of 0.1℃ / min, and keep it for 5h. Then, increase the temperature from 380℃ to 550℃ at a rate of 0.1℃ / min, and keep it for 2h. Finally, decrease the temperature from 550℃ to 150℃ at a rate of 0.2℃ / min, and then cool to room temperature with the furnace.

[0067] After debinding is completed, the final size tolerance accounts for 1.2% of the total size of the sample;

[0068] (3) The sample after debinding molding was subjected to isostatic pressing at a pressure of 200 MPa for 5 min;

[0069] (4) The sample after isostatic pressing was placed on an alumina plate covered with 100-200 mesh corundum powder. The corundum powder was calcined at 1400°C for 2h. A cylindrical hollow brick with a diameter of 30mm and a height of 11mm was placed at the center of the sample, and 100-200 mesh corundum powder was filled in the gap. A matrix powder with the same composition as the sample was placed on the periphery and then placed in a muffle furnace for sintering (the sintering process adopted the conventional textured ceramic sintering process). The final dimensional tolerance accounted for 0.9% of the total size of the sample.

[0070] Example 2

[0071] This embodiment prepares a lead-free thin-walled circular tube textured piezoelectric ceramic, wherein the thin-walled circular tube textured piezoelectric ceramic blank is a lead-free material, and the preparation process and steps are as follows:

[0072] (1) The bottom of a cylindrical alumina crucible is filled with corundum powder calcined at 1400° C. for 2 hours and compacted. The height of the filled corundum powder is 10 mm and the particle size is 150-350 meshes. A rolled lead-free thin-walled circular tubular textured piezoelectric ceramic blank with an inner diameter of Φ=55 mm, a height of h=28 mm, and a wall thickness of t=2.5 mm is placed in the alumina crucible, and a cylindrical hollow brick with a diameter of 45 mm, a height of 5 mm, and a porosity of 50% is placed at the center of the lead-free thin-walled circular tubular textured piezoelectric ceramic blank;

[0073] (2) The gaps formed by the lead-free thin-walled circular tubular textured piezoelectric ceramic blank, the cylindrical alumina crucible and the cylindrical hollow brick were filled with corundum powder with a width of 5 mm and 5 mm respectively, which was calcined at 1400°C for 2 hours. The particle size of the corundum powder was 150-350 meshes. After the excess powder was cleaned, it was placed in a muffle furnace for debinding. The debinding process was as follows:

[0074] First, the temperature was raised from room temperature to 190°C at a rate of 0.2°C / min, and kept for 10 hours. Then, the temperature was raised from 190°C to 240°C at a rate of 0.1°C / min, and kept for 10 hours. Then, the temperature was raised from 240°C to 280°C at a rate of 0.1°C / min, and kept for 5 hours. Then, the temperature was raised from 280°C to 380°C at a rate of 0.1°C / min, and kept for 5 hours. Then, the temperature was raised from 380°C to 550°C at a rate of 0.1°C / min, and kept for 2 hours. Finally, the temperature was lowered from 550°C to 150°C at a rate of 0.4°C / min, and then cooled to room temperature with the furnace.

[0075] After debinding is completed, the final size tolerance accounts for 0.7% of the total size of the sample;

[0076] (3) The sample after debinding molding was subjected to isostatic pressing at a pressure of 100 MPa for 8 min;

[0077] (4) The sample after isostatic pressing was placed on an alumina plate covered with 100-200 mesh corundum powder. The corundum powder was calcined at 1400°C for 2h. A cylindrical hollow brick with a diameter of 5mm and a height of 5mm was placed at the center of the sample, and 100-200 mesh corundum powder was filled in the gap. A matrix powder with the same composition as the sample was placed on the periphery and then placed in a muffle furnace for sintering (the sintering process adopted the conventional textured ceramic sintering process). The final dimensional tolerance accounted for 0.57% of the total size of the sample.

[0078] Example 3

[0079] This embodiment prepares a lead-free thin-walled circular tube textured piezoelectric ceramic, wherein the thin-walled circular tube textured piezoelectric ceramic blank is a lead-free material, and the preparation process and steps are as follows:

[0080] (1) The bottom of a cylindrical alumina crucible is filled with corundum powder calcined at 1400° C. for 2 hours and compacted. The height of the filled corundum powder is 50 mm and the particle size is 150-350 meshes. A rolled lead-free thin-walled circular tubular textured piezoelectric ceramic blank with an inner diameter of Φ=55 mm, a height of h=28 mm, and a wall thickness of t=2.5 mm is placed in the alumina crucible, and a cylindrical hollow brick with a diameter of 20 mm, a height of 30 mm, and a porosity of 52% is placed at the center of the lead-free thin-walled circular tubular textured piezoelectric ceramic blank;

[0081] (2) The gaps formed by the lead-free thin-walled circular tubular textured piezoelectric ceramic blank, the cylindrical alumina crucible and the cylindrical hollow brick were filled with corundum powder with a width of 15 mm and 17 mm, respectively, after being calcined at 1400°C for 2 hours. The particle size of the corundum powder was 150-350 meshes. After the excess powder was cleaned, it was placed in a muffle furnace for debinding. The debinding process was as follows:

[0082] First, increase the temperature from room temperature to 190℃ at a rate of 0.3℃ / min, and keep it for 10h. Then, increase the temperature from 190℃ to 240℃ at a rate of 0.1℃ / min, and keep it for 10h. Then, increase the temperature from 240℃ to 280℃ at a rate of 0.1℃ / min, and keep it for 5h. Then, increase the temperature from 280℃ to 380℃ at a rate of 0.1℃ / min, and keep it for 5h. Then, increase the temperature from 380℃ to 550℃ at a rate of 0.1℃ / min, and keep it for 2h. Finally, decrease the temperature from 550℃ to 150℃ at a rate of 0.5℃ / min, and then cool to room temperature with the furnace.

[0083] After debinding is completed, the final size tolerance accounts for 1.7% of the total size of the sample;

[0084] (3) The sample after debinding molding was subjected to isostatic pressing at a pressure of 150 Mp for 10 min;

[0085] (4) The sample after isostatic pressing is placed on an alumina plate covered with 100-200 mesh corundum powder. The corundum powder is corundum powder calcined at 1400°C for 2h. A cylindrical hollow brick with a diameter of 20mm and a height of 30mm is placed at the center of the sample, and 100-200 mesh corundum powder is filled in the gap. After the matrix powder with the same composition as the sample is placed on the periphery, it is placed in a muffle furnace for sintering (the sintering process adopts the conventional textured ceramic sintering process). The final dimensional tolerance accounts for 1% of the total size of the sample.

[0086] Example 4

[0087] This embodiment prepares a lead-free thin-walled circular tube textured piezoelectric ceramic, wherein the thin-walled circular tube textured piezoelectric ceramic blank is a lead-free material, and the preparation process and steps are as follows:

[0088] (1) The bottom of a cylindrical alumina crucible is filled with corundum powder calcined at 1400°C for 2h and compacted. The height of the filled corundum powder is 45mm and the particle size is 150-350 meshes. The rolled lead-free thin-walled circular tubular textured piezoelectric ceramic blank with an inner diameter of Φ=72.56mm, a height of h=65.3mm, and a wall thickness of t=1.35mm is placed in the alumina crucible, and a cylindrical hollow brick with a diameter of 60mm, a height of 80mm, and a porosity of 48% is placed at the center of the lead-free thin-walled circular tubular textured piezoelectric ceramic blank;

[0089] (2) The gaps formed by the lead-free thin-walled circular tubular textured piezoelectric ceramic blank, the cylindrical alumina crucible and the cylindrical hollow brick were filled with corundum powder with a width of 10 mm and 6 mm, respectively, after being calcined at 1400°C for 2 hours. The particle size of the corundum powder was 150-350 meshes. After the excess powder was cleaned, it was placed in a muffle furnace for debinding. The debinding process was as follows:

[0090] First, increase the temperature from room temperature to 190℃ at a rate of 0.3℃ / min, and keep it for 10h. Then, increase the temperature from 190℃ to 240℃ at a rate of 0.1℃ / min, and keep it for 10h. Then, increase the temperature from 240℃ to 280℃ at a rate of 0.1℃ / min, and keep it for 5h. Then, increase the temperature from 280℃ to 380℃ at a rate of 0.1℃ / min, and keep it for 5h. Then, increase the temperature from 380℃ to 550℃ at a rate of 0.1℃ / min, and keep it for 2h. Finally, decrease the temperature from 550℃ to 150℃ at a rate of 0.5℃ / min, and then cool to room temperature with the furnace.

[0091] After debinding is completed, the final size tolerance accounts for 0.9% of the total size of the sample;

[0092] (3) The sample after debinding molding was subjected to isostatic pressing at a pressure of 200 MPa for 5 min;

[0093] (4) The sample after isostatic pressing is placed on an alumina plate covered with 100-200 mesh corundum powder. The corundum powder is corundum powder calcined at 1400°C for 2h. A cylindrical hollow brick with a diameter of 60mm and a height of 80mm is placed at the center of the sample, and 100-200 mesh corundum powder is filled in the gap. After the matrix powder with the same composition as the sample is placed on the periphery, it is placed in a muffle furnace for sintering (the sintering process is consistent with the conventional textured ceramic sintering process). The final dimensional tolerance accounts for 1.24% of the total size of the sample.

[0094] A series of performance tests were performed on the products prepared in Examples 1-4, as follows:

[0095] like Figure 1 As shown, Figure 1 (a)- Figure 1 (d) is a picture of the sample blank after debinding and molding of Examples 1-4. It can be seen from the figure that the sample shape remains intact, shrinks evenly in the radial and longitudinal directions, and still maintains a standard round tube shape. The inner and outer surfaces of the sample are smooth and defect-free.

[0096] like Figure 2 As shown, Figure 2 (a)- Figure 2 (d) is a picture of the sample of Example 1-4 after sintering and forming without any processing. It can be seen from the figure that the shape of the sample remains intact, basically a standard round tube shape, and the inner and outer surfaces of the sample are smooth and defect-free.

[0097] like Figure 3 , which is the XRD diagram of the sample of Example 3 after sintering, it can be seen from the figure that the texture degree of this lead-free thin-walled circular tubular textured piezoelectric ceramic is 94.19%.

[0098] like Figure 4 As shown, it is a cross-sectional scan of the sample of Example 3 after sintering. It can be seen from the figure that the grain size of the BNT ceramic after induction by the BT template is significantly increased, which indicates that the BT template successfully induces the directional growth of the BNT ceramic matrix grains.

[0099] Comparative Example

[0100] In order to explore the influence of different parameters in the preparation process of the present invention on the quality of the final product of the present invention, the following comparative experiments were conducted. Different lead-free thin-walled circular tubular textured piezoelectric ceramics were prepared in the following comparative examples, as follows:

[0101] Comparative Example 1

[0102] This comparative example prepares a lead-free thin-walled cylindrical textured piezoelectric ceramic similar to that of Example 1, with the only difference being that in step (1), the particle size of the corundum powder used is 100 mesh, and the other parameters are the same as those of Example 1.

[0103] Comparative Example 2

[0104] This comparative example prepares a lead-free thin-walled cylindrical textured piezoelectric ceramic similar to that of Example 1, with the only difference being that in step (1), the particle size of the corundum powder used is 400 mesh, and the other parameters are the same as those of Example 1.

[0105] The products of Examples 1 and 2 were tested as follows:

[0106] Figure 5The figures are of the sample blanks after debinding and molding of Comparative Examples 1 and 2. Compared with the sample blanks prepared in Examples 1-4, when the particle size of the corundum powder is replaced with 100 mesh or 400 mesh, the samples will crack and bubble, causing the sample debinding to fail.

[0107] Comparative Example 3

[0108] This comparative example prepares a lead-free thin-walled circular tubular textured piezoelectric ceramic similar to Example 1, with the only difference being that in step (2), no staged heating is performed, but the temperature is directly raised from room temperature to 550°C at a heating rate of 0.05°C / min. After debinding for 6 hours, the temperature is then lowered from 550°C to room temperature at a cooling rate of 0.1°C / min.

[0109] The product prepared in Comparative Example 3 was subjected to performance tests. Figure 6 As shown, it is a sample blank image after debinding and molding of comparative example 3. Compared with examples 1-4, the surface of the sample is severely cracked. This is because the different reactions of organic matter in the sample at different temperature ranges are not taken into account. As a result, the gas generated by the volatilization of organic matter during the debinding process breaks through the sample surface.

[0110] Comparative Example 4

[0111] This comparative example prepares a lead-free thin-walled circular tubular textured piezoelectric ceramic similar to Example 1, except that in step (1), no cylindrical hollow bricks are placed inside the lead-free thin-walled circular tubular textured piezoelectric ceramic blank, but the entire blank is filled with corundum powder.

[0112] The product prepared in Comparative Example 4 was subjected to performance tests. Figure 7 As shown in the figure, it is a blank image of the sample after debonding molding of comparative example 4. It can be seen from the figure that there are no defects on the surface of the sample, but the sample is severely deformed and cannot maintain the original tubular shape. This is because the sample is only filled with powder inside during the shrinkage process, and there is no support inside to serve as a solid. When the sample shrinks, the powder retreats to anisotropy, causing the shape of the sample to change, which is free shrinkage.

[0113] Comparative Example 5

[0114] This comparative example prepares a lead-free thin-walled circular tubular textured piezoelectric ceramic similar to Example 1, with the only difference being that in step (2), only cylindrical hollow bricks and cylindrical alumina crucibles are placed inside and outside the lead-free thin-walled circular tubular textured piezoelectric ceramic blank, and corundum powder is not filled in the gaps and at the bottom.

[0115] The product prepared in Comparative Example 5 was subjected to performance tests. Figure 8As shown in the figure, it is a picture of the sample blank after debinding and molding of comparative example 5. It can be seen from the figure that there is serious bulging on the surface of the sample. This is because there is no powder filling at the bottom and the gap, and the volatilization of organic matter in the debinding process cannot be excessive, resulting in defects such as bulging on the surface of the sample; in addition, the sample is seriously deformed. This is because there is no powder support between the inside of the sample and the hollow brick. This is because the organic matter softens during the debinding process, the sample shrinks inconsistently in all directions, and the combined action of gravity causes the sample to be seriously deformed and irregularly deformed.

[0116] Comparative Example 6

[0117] In this comparative example, a lead-free thin-walled cylindrical textured piezoelectric ceramic similar to that in Example 1 is prepared, except that the filled corundum powder is completely replaced with barium sulfate powder, and the other parameters are the same as those in Example 1.

[0118] The product prepared in Comparative Example 6 was subjected to performance tests. Fig. 9 As shown, this is a picture of the sample blank after debinding molding of comparative example 6. It can be seen from the figure that the sample is broken, the surface is severely peeled, and the powder and the sample are severely adhered.

[0119] Comparative Example 7

[0120] This comparative example prepares a lead-free thin-walled circular tubular textured piezoelectric ceramic similar to that of Example 1, with the only difference being that in step (2), the powder filling width is changed to 3 mm.

[0121] The product prepared in Comparative Example 7 was subjected to performance tests. Fig.10 As shown, it is a blank image of the lead-free thin-walled circular tube textured piezoelectric ceramic after debinding molding in comparative example 7, wherein Fig.10 (a) is the macroscopic morphology of the sample after debinding. Fig.10 (b) is the internal powder status diagram; Fig.10 (b) It can be seen that the corundum powder has agglomeration phenomenon. This is because the filling width is small, so the gas generated by the organic matter inside the sample at high temperature directly breaks through the sample surface, causing the corundum powder to agglomerate; Fig.10 In (a), it can be clearly observed that the sample has bubbling and cracking.

[0122] Finally, it should be noted that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein with equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the scope of protection of the claims of the present invention.

Claims

1. A method for preparing a lead-free thin-walled circular tubular textured piezoelectric ceramic, characterized in that: Follow the steps below in order: (1) filling the bottom of a cylindrical alumina crucible with a height of 10 to 50 mm with corundum powder and compacting it, placing the rolled lead-free thin-walled circular tubular textured piezoelectric ceramic blank in the alumina crucible filled with corundum powder, and placing a cylindrical hollow brick at the center of the lead-free thin-walled circular tubular textured piezoelectric ceramic blank; (2) filling the gaps formed by the lead-free thin-walled circular tubular textured piezoelectric ceramic blank, the cylindrical alumina crucible and the cylindrical hollow brick with corundum powder, cleaning the excess powder and placing it in a muffle furnace for debinding; (3) isostatic pressing the sample after debinding; (4) The sample after isostatic pressing is placed on an alumina plate covered with corundum powder. A cylindrical hollow brick is placed at the center of the sample, and corundum powder is filled in the gap. Matrix powder with the same composition as the sample is placed on the periphery and placed in a muffle furnace for sintering.

2. The method for preparing a lead-free thin-walled circular tubular textured piezoelectric ceramic according to claim 1, characterized in that: In step (1), the corundum powder is a powder calcined at 1400° C. for 2 hours, and the particle size of the powder is 150 to 350 meshes.

3. The method for preparing a lead-free thin-walled circular tubular textured piezoelectric ceramic according to claim 1, characterized in that: In step (1), the hollow brick is made of high temperature resistant porous mullite with a porosity of 48-52%; the hollow brick has a diameter of 5-60 mm and a height of 5-80 mm.

4. The method for preparing a lead-free thin-walled circular tubular textured piezoelectric ceramic according to claim 1, characterized in that: In step (2), the corundum powder is a powder calcined at 1400° C. for 2 hours, and the powder particle size is 150 to 350 meshes; the filling powder width is 5 to 25 mm.

5. The method for preparing a lead-free thin-walled circular tubular textured piezoelectric ceramic according to claim 1, characterized in that: In step (2), the debinding process is carried out in the following order: (a) The first heating stage: from room temperature to 190°C, and keep the temperature for 10 hours; (b) The second heating stage, from 190°C to 240°C, kept for 10 h; (c) The third heating stage, from 240°C to 280°C, and kept for 5 hours; (d) The fourth heating stage, from 280°C to 380°C, and kept for 5 hours; (e) The fifth heating stage, from 380°C to 550°C, kept for 2 h; (f) Cooling stage: the temperature is reduced from 550°C to 150°C, and then cooled to room temperature in the furnace.

6. The method for preparing a lead-free thin-walled circular tubular textured piezoelectric ceramic according to claim 4, characterized in that: In step (2), the heating rate of the first heating stage is 0.1-0.3°C / min; the heating rate of the second heating stage is 0.1°C / min; the heating rate of the third heating stage is 0.1°C / min; the heating rate of the fourth heating stage is 0.1°C / min; the heating rate of the fifth heating stage is 0.1°C / min; and the rate of the cooling stage is 0.2-0.5°C / min.

7. The method for preparing a lead-free thin-walled circular tubular textured piezoelectric ceramic according to claim 1, characterized in that: In step (3), the isostatic pressure is 100-200 MPa and the time is 5-10 min.

8. The method for preparing a lead-free thin-walled circular tubular textured piezoelectric ceramic according to claim 1, characterized in that: In step (4), the corundum powder is a powder calcined at 1400° C. for 2 hours, and the powder particle size is 100 to 200 meshes.

9. The method for preparing a lead-free thin-walled circular tubular textured piezoelectric ceramic according to claim 1, characterized in that: In step (4), the diameter of the hollow brick is 5 to 60 mm and the height is 5 to 80 mm.

10. A method for preparing a lead-free thin-walled circular tubular textured piezoelectric ceramic according to any one of claims 1 to 9, characterized in that: The wall thickness t of the lead-free thin-walled circular tubular textured piezoelectric ceramic is less than or equal to 2.5 mm; the texture degree of the lead-free thin-walled circular tubular textured piezoelectric ceramic is 94.19%.

Citation Information

Patent Citations

  • Molding method and special die for manufacturing ceramic thin-walled tubes

    CN101733818A

  • Dumping and sintering process for 3D printing ceramic body

    CN106316369A

  • Multilayer lead-free piezoelectric ceramic as well as preparation method and application thereof

    CN116063076A

  • High-performance tubular textured ceramic, preparation method and application

    CN118164758A

  • Bottomed cylindrical sintered ceramic material and its production

    JP2000086351A